2023
DOI: 10.1128/msystems.00535-23
|View full text |Cite
|
Sign up to set email alerts
|

Genome characteristics of the optrA -positive Clostridium perfringens strain QHY-2 carrying a novel plasmid type

Ke Wu,
Zhe Li,
Mingjin Fang
et al.

Abstract: Clostridium perfringens is a bacterial species of importance to both public and animal health. The gene optrA is the first gene that confers resistance to the tedizolid, a last-resort antimicrobial agent in human medicine. Herein, we whole-genome sequenced and analyzed one optrA -positive C. perfringens strain QHY-2 from Tibetan sheep in Qinghai province and identified one optrA plasmid pQHY-2. The plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In previous reports, the optrA gene was detected in E. faecalis at a higher rate than in E. faecium [ 52 ]. It has been found that the optrA gene can integrate into the genome (plasmids or chromosomes) of enterococci [ 53 , 54 ], Vagococcus lutrae [ 51 ], Clostridium perfringens [ 55 ], Streptococcus suis [ 56 ], and other species. In this study, we identified that the chromosomal optrA was present in the Tn 6674 -like platform, which had been reported in the linezolid-resistant E. faecalis isolated from food-producing animals [ 57 ] and surface water [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, the optrA gene was detected in E. faecalis at a higher rate than in E. faecium [ 52 ]. It has been found that the optrA gene can integrate into the genome (plasmids or chromosomes) of enterococci [ 53 , 54 ], Vagococcus lutrae [ 51 ], Clostridium perfringens [ 55 ], Streptococcus suis [ 56 ], and other species. In this study, we identified that the chromosomal optrA was present in the Tn 6674 -like platform, which had been reported in the linezolid-resistant E. faecalis isolated from food-producing animals [ 57 ] and surface water [ 58 ].…”
Section: Discussionmentioning
confidence: 99%